Rethinking mechanical heart valves in the aortic position: new paradigms in design and testing - Chakraborty, Sreyashi; Simon, Melinda G.; Bellofiore, Alessandro (Frontiers in Cardiovascular Medicine, 2025)
Bileaflet mechanical heart valves (MHV) remain a viable option for aortic valve replacement, particularly for younger patients and patients from low- and middle-income countries and underserved communities. Despite their exceptional durability, MHV recipients are at increased risk of thromboembolic complications. As such, the development of the next generation of MHVs must prioritize improved thromboresistance and aim for independence from anticoagulant therapy. However, innovation in MHV design faces several challenges: strict performance and biocompatibility requirements, limited understanding of the mechanisms underlying MHV thrombosis, and a lack of effective testing methodologies to assess how design variations impact both hemodynamic performance and thrombogenicity of MHVs. This paper reviews the emerging paradigms in MHV design, materials and surface modifications that may inspire the development of a new generation of MHVs for aortic valve replacement. We also discuss challenges and opportunities in developing experimental and numerical approaches to achieve a more comprehensive understanding of MHV flow features and the mechanisms of flow-induced blood clotting.